Isolation, structure and magnetic properties of two novel core–shell 3d–4f heterometallic nanoscale clusters. Issue 3 (20th December 2016) - Lin, Qingfang; Zhang, Yu; Cheng, Weiwei; Liu, Ying; Xu, Yan
Abstract : Two novel core–shell Ln–Ni (Ln = Nd, Pr) nanosized clusters exhibit discrete dumbbell-shaped and bowknot-like architecture. Abstract : Two novel core–shell Ni–Ln nanosized clusters, Na4 (H3 O)4 [Nd38 Ni42.5 (IDA)42 (OAc)4 (CH3 CH2 OH)2 (CO3 )18 (μ3 -OH)62 (μ3 -O)6 (H2 O)12 ]Cl6 ·26H2 O (1 ) and Na[Pr42 Ni38 (μ3 -OH)71 (μ3 -O)4 (IDA)38 (NH2 CH2 COO)2 (OAc)2 (CH3 CH2 OH)2 (CO3 )16 (H2 O)6 Cl7 ]Cl3 ·37H2 O (2 ) (IDA = iminodiacetate), were successfully prepared using the Cl − anion and the flexible ligand iminodiacetic acid. Structural analysis indicates that the discrete dumbbell-shaped 3d–4f heterometallic cluster in1 is constructed from two Nd19 Ni21 clusters connected by one NiO6 unit, whereas the bowknot-shaped nanosized cluster is composed of two Pr19 Ni19 clusters ligated by two Pr2 units and CO3 2− anions. The formation of both compounds indicates that Cl − ions play important roles and act not only as balance anions but also as template and bridging ligands. The magnetic properties of compounds1 and2 were investigated, and it was revealed that they display dominant antiferromagnetic exchange.